A raising analysis of the Dutch passive - van Noord, Gertjan; Kordoni, Valia (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
This paper focuses on passive constructions in Dutch. Specifically, we focus onworden, as well as krijgen passives in Dutch, for which wepropose a uniform, raising analysis in HPSG. We also show that such an analysiscan be carried over to account for passives cross-linguistically. Specifically,we look at corresponding structures in German and show that there is no needfor a dual raising and control analysis for the German ˋˋagentive''(werden) and the German ˋˋdative'' (kriegen) passives,respectively, as has been proposed in Müller (2002) and Müller (2003).